2020
DOI: 10.3390/jcm9093013
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Quantitative Analysis of Blood-Brain Barrier Disruption Measured Using Contrast-Enhanced Magnetic Resonance Imaging to Predict Neurological Prognosis in Out-of-Hospital Cardiac Arrest Survivors: A Preliminary Study

Abstract: We aimed to evaluate neurological outcomes associated with blood-brain barrier (BBB) disruption using contrast-enhanced magnetic resonance imaging (CE-MRI) in out-of-hospital cardiac arrest (OHCA) survivors. This retrospective observational study involved OHCA survivors who had undergone CE-MRI for prognostication. Qualitative and quantitative analyses were performed using the presence of BBB disruption (pBD) and the BBB disruption score (sBD) in CE-MRI scans, respectively. For the sBD, 1 point was assigned fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Brain DWI was performed using a 3T scanner (Achieva, Philips Healthcare, Amsterdam, The Netherlands) before TTM. The imaging protocol and analysis used were the same as those published previously [ 14 , 15 , 16 ]. Previous studies used the percentage of voxels (PV) below different ADC thresholds and reported that PV 400 (percentage of voxels <400 × 10 −6 mm 2 /s) showed the highest odds ratio value when predicting the poor prognosis of a patient [ 14 ]; therefore, we also used PV 400.…”
Section: Methodsmentioning
confidence: 99%
“…Brain DWI was performed using a 3T scanner (Achieva, Philips Healthcare, Amsterdam, The Netherlands) before TTM. The imaging protocol and analysis used were the same as those published previously [ 14 , 15 , 16 ]. Previous studies used the percentage of voxels (PV) below different ADC thresholds and reported that PV 400 (percentage of voxels <400 × 10 −6 mm 2 /s) showed the highest odds ratio value when predicting the poor prognosis of a patient [ 14 ]; therefore, we also used PV 400.…”
Section: Methodsmentioning
confidence: 99%
“…The primary mechanism of brain injury is closely related to the time window of ischaemia and hypoxia caused by the interruption of blood flow after CA and irreversible damage occurs when cerebral blood flow is completely interrupted for more than 5 minutes. Severe brain blood barrier disruption is also strongly associated with poor neurological outcomes (8). After ROSC, the brain experiences reperfusion injury causing secondary injury.…”
Section: Brain Injury Mechanism After Camentioning
confidence: 99%